ANALISIS PENGARUH EKUITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN (Studi Pada Konsumen Minuman Isotonik Pocari Sweat di Pontianak) - PUTRI B11108198, NOVELLA TANTIA (Jurnal Manajemen Update, 2014)
In the middle of rush competition in the bussines world this day, one of the company's efforts to differentiate their products with others competitors  is to provide their brand name. In this research the authors aimed to determine how much impact of brand equity to purchasing decision partially and simultaneously. It’s important when a brand has all the aspects contained in brand equity, because it can provide long term benefits to companies both from the aspect of the products, people, systems, sales, and company. This research used a descriptive and quantitative research method. To gain the data researcher using multiple regression analysis by using statistical hypothesis f test and t test. While in obtaining the data, the authors deploy a list of questions in a structured and related to the problem. The sample are the respondents who already over 17 years old and already consume isotonic drinks brand Pocari Sweat in Pontianak. The results of this study indicate that: (1) There is a positive and significant effect partially between Brand Equity aspects and the purchase decision of isotonic drink Pocari Sweat in Pontianak. (2) There is a positive and significant effect simultaneously between Brand Equity aspects and the purchase decision of isotonic drink Pocari Sweat in Pontianak. (3) Each of independent variable on the average rate has a positive impact on the purchase decision process of isotonic drink Pocari Sweat in Pontianak. The suggestions from this research that researchers can convey are as follows: (1) Currently the aspects that contained on brand equity has been implemented quite well in an product isotonic drink Pocari Sweat, but the company is expected to continue improve the values ​​that have been created, as to increase the prestige of the brand isotonic drink Pocari Sweat itself. And may continue to increase the positive value from the consumer, by fulfilling the expectations desired from the consumers. (2) For further research of Brand Equity is expected to examine from the perspective of the company or management not only from the perspective of the consumer and purchasing decisions. Keyword: Brand Equity, Purchasing Decisions, Marketing Managements